2001
DOI: 10.1007/s002210000595
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age on weight-bearing joint reposition sense of the knee

Abstract: Knee joint-position sensitivity has been shown to decline with increasing age, with much of the research reported in the literature investigating this age effect in non-weight-bearing (NWB) conditions. However, little data is available in the more functional position of weight-bearing conditions. The objective of this study was to identify the influence of age on the accuracy and nature of knee joint-position sense (JPS) in both full weight-bearing (FWB) and partial weight-bearing (PWB) conditions and to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
82
4
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 0 publications
8
82
4
1
Order By: Relevance
“…These systems are likely to go through functional changes with ageing, given that older adults showed a poorer performance than young adults in all assessments. The differences found between the groups are consistent with the findings of previous studies where older adults were found to have a diminished acuity and sensitivity to visual contrast 22,23 , smaller tactile sensitivity 24,25 and proprioceptive differences [26][27][28] , when compared to young adults. The results of motor system assessments also confirmed previous results, which indicated a smaller knee and ankle joint torque among older people, when compared to younger people 27,[29][30][31][32] .…”
Section: Discussionsupporting
confidence: 90%
“…These systems are likely to go through functional changes with ageing, given that older adults showed a poorer performance than young adults in all assessments. The differences found between the groups are consistent with the findings of previous studies where older adults were found to have a diminished acuity and sensitivity to visual contrast 22,23 , smaller tactile sensitivity 24,25 and proprioceptive differences [26][27][28] , when compared to young adults. The results of motor system assessments also confirmed previous results, which indicated a smaller knee and ankle joint torque among older people, when compared to younger people 27,[29][30][31][32] .…”
Section: Discussionsupporting
confidence: 90%
“…However, alternative methods involving repeated measurements of single joint positioning rather than the whole limb were not functionally relevant [3,5,8,10]. Furthermore, due to the design of the experiment, the data is only relevant to those with upper limb CRPS.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies showed greater errors in older adults' joint position matching as compared to young ones (Adamo et al 2007(Adamo et al , 2009Barrack et al 1983;Bullock-Saxton et al 2001;Hurley et al 1998;Kaplan et al 1985;Madhavan and Shields 2005;Marks et al 1993;Petrella et al 1997;Tsang and Hui-Chan 2004;Verschueren et al 2002;You 2005). To explain this result, authors mentioned muscle spindles (Swash and Fox 1972;Kararizou et al 2005;Liu et al 2005;Rosant et al 2007) and nervous system (CruzSánchez et al 1998;Giorgio et al 2010) degenerations that have been evidenced to occur in ageing.…”
Section: Introductionmentioning
confidence: 99%
“…The three main matching paradigms are presented in this introduction. First, in ipsilateral and contralateral remembered matching tasks (Goble et al 2005), a subject's limb is actively or passively displaced to the reference position and held for 2-3 s (Adamo et al 2009;Barrack et al 1983;Bullock-Saxton et al 2001;Petrella et al 1997;Skinner et al 1984;Tsang and Hui-Chan 2004), 5 s (Deshpande et al 2003;Goble et al 2011;Hurley et al 1998;Marks 1996;Marks et al 1993;Pickard et al 2003;Westlake et al 2007), or 15 s (Kaplan et al 1985) prior to being returned to its starting angle. Next, the participant is asked to identify the reference position with the same (ipsilateral) or other (contralateral) limb during an active or passive movement based on proprioceptive memory.…”
Section: Introductionmentioning
confidence: 99%